The Optimization Conditions of Friction Stir Welding (FSW) for Different Rotational and Weld speeds - Takhakh, Ayad M.; Abdullah, Asmaa M. (Nahrain University College of Engineering Journal, 2012)
The effect of welding parameters on mechanical properties of aluminum alloy 3003 H14 Friction stir-welded (FSW) joints were investigated in the present study. Different welded specimens were produced by employing variable rotating speeds (1000, 1250, 1500, 2000 r.p.m.), and welding speeds (20, 40, 60, 80 mm/min). Microhardness measurements and tensile strength of the produced joints were tested. The experimental results indicated that the process parameters have a significant effect on mechanical properties of joints. The optimum results of the weld gained at the parameter 80mm/min weld speed and 1500 rpm rotation speed where the efficiency reaches to 89% of the ultimate tensile strength of the parent metal